1991
DOI: 10.1210/jcem-73-3-549
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Endogenous Catecholamine Synthesis Augments Early Follicular Phase Luteinizing Hormone Secretion*

Abstract: The physiological role of catecholamines, particularly dopamine and norepinephrine, in the regulation of gonadotropin secretion in humans is unclear. We administered the tyrosine hydroxylase inhibitor alpha-methyl-p-tyrosine (AMPT, 500 mg at 800 and 1000 h) to five women in the early follicular phase of the menstrual cycle and compared LH secretion patterns to those in five untreated controls. Commencing at 800 h, blood was drawn every 15 min for LH and PRL measurements until 1600 h. AMPT elevated PRL concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…] Bódis, Department of Obstetrics and Gynecology, University Medical School of Pécs, H-7624Pécs, Édesanyák útja 17, Hungary Plosker et al (1) reported augmented LH levels after ae-methyl-p-tyrosine treatment in women. They con¬ cluded that increased LH secretion after inhibition of catecholamine synthesis was due to an increased LH pulse amplitude.…”
mentioning
confidence: 99%
“…] Bódis, Department of Obstetrics and Gynecology, University Medical School of Pécs, H-7624Pécs, Édesanyák útja 17, Hungary Plosker et al (1) reported augmented LH levels after ae-methyl-p-tyrosine treatment in women. They con¬ cluded that increased LH secretion after inhibition of catecholamine synthesis was due to an increased LH pulse amplitude.…”
mentioning
confidence: 99%
“…To further complicate matters, steroid treatment shifts the response to NE from inhibition to stimulation in the rat [26,43], but this may reflect activation of neural mechanisms for induction of the LH surge [26]. On the other hand, humans may be similar to the sheep, because there is suggestive evidence that a,-adrenergic mechanisms inhibit LH pulse amplitude in women [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that administration of AMT increases endogenous prolactin levels both in animals and humans [6][7][8][9]. Thus, measuring AMT concentrations in plasma could help establish AMT pharmacokinetics and also aid in potentially developing a pharmacoki- netic/pharmacodynamic (PK/PD) model between AMT and prolactin.…”
Section: Introductionmentioning
confidence: 99%